Biological treatment of textile-dye wastewater fate of azo dye and dye degradation products in anaerobic-aerobic systems - Consignado, Lenita J.
The use of an anaerobic-aerobic treatment system for textile-dye wastewater was examined. The treatment system consisted of an upflow anaerobic sludge bed (UASB) reactor followed by an aerobic sequencing batch reactor (SBR). Synthetic desize-dye wastewater consisting of hydrolyzed starch and Reactive Red 235 was used in the study. The aerobic biodegradability of Reactive Red 235, Reactive Blue 235, and Reactive Yellow 168 was also investigated.